The essence of crime: Contagious transmission from those who have committed moral transgressions. (1st August 2016) - Tapp, Caley; Occhipinti, Stefano
Abstract : Across four studies, we investigated the relationship between moral contagion and disgust. Study 1 established that the contamination effect is unique to transgressions that fall within the moral domain. Study 2 replicated this effect and further showed that the underlying mechanism is intimately related to disgust, as disgust was found to uniquely mediate the relationship between moral transgressions and contamination responses. In Study 3, disgust was again found to mediate this relationship. In addition, the results of Study 3 show that the moral contagion effect was not dependent upon the presence of a core disgust cue within the transgression. In Study 4, we investigated whether or not moral contagion leads to behavioural avoidance. Results show that behavioural avoidance only occurred when the moral transgression contained a core disgust cue. Taken together, the results of our studies show that disgust plays a key role in moral contagion processes. However, the difference in findings between the thought experiments (Studies 1–3) and the behavioural experiment (Study 4) identifies a need for further research to examine the conditions under which moral contagion leads to behavioural avoidance.